RANCANG BANGUN SISTEM INFORMASI DATA PEGAWAI BERBASIS WEB MENGGUNAKAN FRAMEWORK BOOTSTRAP (STUDI KASUS DINAS PEMBERDAYAAN PEREMPUAN ANAK DAN KELUARGA BERENCANA MAJALENGKA) - Helmi Yahya; Nunu Nurdiana (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
The development of information systems has been rapid and evident in this modern era, with almost all fields of activity utilizing a system to support the quality of life in society. Information systems can be seen as a way out to facilitate the execution of activities and achieve a goal optimally. Information systems consist of three components: humans, information technology, and work procedures that can process, store, analyze, and disseminate information to achieve a goal. A case study in this research is conducted at the Office of Women Empowerment, Children, and Family Planning of Majalengka District. The Office of Women Empowerment, Children, and Family Planning is led by a department head who is under the responsibility of the Regent through the Regional Secretary. Their main duties involve formulating, organizing, nurturing, and evaluating the development and implementation of local policies in the fields of women empowerment, child protection, and family planning, which include strengthening, empowering, and protecting women, improving family quality, protecting and fulfilling children's rights, and providing family planning services.